Sumando Inheritance to Natal Muslim Community, Mandailing Natal District (Comparative Study of Islamic and Customary Law) - Nasution, Muhammad Hasan; Siregar, Syahmedi; Harahap, Muhammad Yadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Sumando is the joining of a husband to his wife’s family after the marriage. In the Natal District community system, a marriage bond will create inheritance. The difference is, the distribution of inheritance is carried out based on custom where women are the heirs. Daughters as the successors of descendants receive honor in various customary events, including in the distribution of inheritance. If this is viewed from the Islamic inheritance law system, this surely seems contradictory. This is because in Islam, the share of men heirs is twice as much as that of women. This research was a descriptive analysis with qualitative methods. This research showed that women in Sumando society are prioritized to get inheritance, but men were also if the inherited property was in the form of money, not goods. The Sumando indigenous people of Natal District still upheld the matrilineal system. Meanwhile, the distribution of inheritance based on Islamic law was patrilineal-martilineal. This meant that men and women have the right to inherit according to the provisions of their respective sections.